Effect of space holders on fabrication of porous titanium alloy-hydroxyapatite composite through powder injection molding - Farrahshaida Mohd Salleh,; Abu Bakar Sulong,; Muhammad Rafi Raza,; Norhamidi Muhamad,; Lim, Tsiu Fhang (Penerbit Universiti Kebangsaan Malaysia, 2017)
Powder injection molding (PIM) is able to produce porous titanium alloy/hydroxyapatite composite through the space holder technique. Thermal debinding and sintering processes were the main challenges due to different properties of metal and ceramic in producing such composite. This study focused on the effect of different space holders on the physical and mechanical properties of debound and sintered porous titanium aloi/hydroxyapatite composite. The feedstock is containing of 80 wt. % of titanium alloy/hydroxyapatite with 20 wt. % of space holders such as sodium chloride (NaCl) and polymethylmethacrylate (PMMA), respectively. The binders were then removed from the injected samples by two stages of debinding; solvent and thermal debinding. The sintering was performed at three different temperatures 1100oC, 1200oC and 1300oC at a heating rate of 10oC /min and holding time of 5 h. It was found that the samples containing PMMA space holder was fractured after sintering. While, the samples containing NaCl space holder successfully formed pores and not fractured. At sintering temperature of 1300oC, the density, compressive strength and porosity volume percentages for the sintered sample containing NaCl space holder were 3.05 g/cm3, 91.7 MPa. and 11.9 vol%, respectively.